2022
DOI: 10.3126/ajms.v13i7.42957
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study to assess the clinical profile of acute appendicitis and evaluate the combined use of modified Alvarado score and ultrasonography in a tertiary care center in India

Abstract: Background: Acute appendicitis is one of the most common causes of acute abdomen presentation to the hospital. If not treated in time, it may lead to perforation. Alvarado score is a clinical scoring system used in the diagnosis of acute appendicitis. The score is based on laboratory findings, clinical symptoms, and signs. We stipulate that ultrasonography and modified Alvarado score (MAS) can be synchronously and concomitantly be used to reach a trustable diagnosis of acute appendicitis. Aims and Objectives: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…In a study by Kanaskar et al, the combined use of MAS and USG reported a sensitivity of 80.64% [ 13 ]. The current study findings corroborate the findings of other studies [ 15 - 17 ], adding to the evidence of the practice of using MAS and USG of the abdomen in diagnosing acute appendicitis.…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Kanaskar et al, the combined use of MAS and USG reported a sensitivity of 80.64% [ 13 ]. The current study findings corroborate the findings of other studies [ 15 - 17 ], adding to the evidence of the practice of using MAS and USG of the abdomen in diagnosing acute appendicitis.…”
Section: Discussionsupporting
confidence: 91%